IT Consumerization & Enterprise Architecture: An Exploratory Case Study - Zhou, Eric (Université d'Ottawa / University of Ottawa, 2017)
IT Consumerization is the phenomenon of consumer-originated and consumer-oriented technologies entering organizations and their corresponding organizational impacts, risks, and opportunities. IT Consumerization has fundamentally changed the way organizations respond to the technology needs of business users as well as the corresponding governance, management, and operational maintenance of information technology. Enterprise Architecture (EA), a practice and body of knowledge that views organizations and enterprises through architectural layers, has been posited as an effective tool in supporting the needs of IT Consumerization. This thesis addresses the question of what roles EA can play in the context of IT Consumerization as well as the general effectiveness and comprehensiveness of current EA frameworks in addressing IT Consumerization needs. Using a single case study design, this research study applied directed content analysis and a deductive thematic analysis approach to answer these questions. The initial set of codes and themes were derived from sensitizing concepts within The Open Group Architectural Framework (TOGAF). Findings from this research suggest that IT Consumerization is a complex domain characterized with unpredictability, unknown decision variables, and no single correct answer in the context of problem solving and decision making. Our research suggests that in order for an EA practice to help in IT Consumerization initiatives, organizations must ensure that EA practices are not limited to technical problem solving, and that they have the resources and skills required for business problem solving. While EA has often been positioned as an information technology function within many organizations, we argue that based on our findings, EA’s role within organizations can go beyond this traditionally technical focus, to include both advisory and strategic roles leveraging business skillsets to solve business problems. Our EA role framework is a significant departure from the widespread belief that EA practices start at the translation of business strategy to technology strategy, by proposing that EA can play a valuable role earlier in strategic processes such as business strategy development, direction setting, and change prioritization. This inquiry highlights some of the key interrelationships between EA and IT Consumerization.
Keywords: IT Consumerization; Enterprise Architecture